Pertumbuhan dan tanggapan terhadap penyakit karat (puccinia kuehnii) sembilan klon tebu (saccharum officinarum L.) yang diinfeksi jamur mikoriza arbuskular - , WENNY ISMAYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Arbuscular Mycorrhizal Fungi (AMF) have a high potential to improve plant growth, production, and plant resistance to pathogens, therefore AMF often used as a biofertilizer. This study was conducted to revealed the level of AMF infectivity on sugarcane clones, effects of AMF inoculation on plant growth responses, and plant resistance to orange rust disease, as the basic of plant breeding program with low input of chemical fertilizers. The research was started in December 2012 to July 2013 in a plastic house at Condongcatur and Laboratory of Agriculture Micology, Faculty of Agriculture, Gadjah Mada University. This research was arranged in Randomized Completely Block Design (RCBD) with 2 factors and 3 replications. The first factor was sugarcane clones consists of 9 levels, i.e. 6219, 6202, 6239, 6525, 6535, PS92- 752, BL, PS881, and PSJK922. The second factor were inoculation of AMF and without inoculation of AMF. The data were analized by analysis of variance (Anova) applying level of significance Î± = 5%. Whenever the significant differences among treatments were found, further analysis was carried out by applying Duncanâs Multiple Range Test (DMRT) of Î± = 5%. The results showed that the AMF infectivity in nine sugarcane clones was more than 70%. AMF may improve sugarcane growth in terms of plant height, number of tillers, the green level of leaves, fresh weight, and dry weight. Generally, 6239 clone has good response with the number of dry weight were higher from the others. Based on the resistance scoring, sugarcane clones 6202, 6219, and BL were moderate resistance of orange rust disease, while sugarcane clones 6239, 6525, 6535, PS92-752, PS881, and PSJK922 were moderate susceptible of orange rust disease. AMF may increase resistance of 6239 clone to orange rust disease from moderate susceptible became moderate resistance. 6239 clone can be used in sugarcane breeding programs that have a good symbiosis with JMA.